Repeated broad ligament hematomas managed by uterine artery embolization: time to execute - Panda, Subrat; Sharma, Nalini; Phukan, Pranjal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Selective arterial embolization (SAE) of the uterine arteries is an alternative to surgery when medical management fails in cases of intractable posrtpartum haemorrhage. It is highly efficacious with low complication rate. Here we report a case of repeated broad ligament haematoma managed by selective uterine artery embolization. Present case 28year old P4L4 was referred from a district hospital as post LSCS case with broad ligament haematoma. Patients general condition was very poor at the time of admission. She underwent laparotomy twice and finally uterine artery embolization for repeated broad ligament haematoma and responded. Massive obstetric haemorrhage remains a significant cause of maternal morbidity and mortality. The threshold for uterine artery embolization (UAE) in women with obstetric haemorrhage should be low, as it is coupled with a high clinical effectiveness rate, low complication rate and preservation of fertility. However, it requires an infrastructure, multidisciplinary approach, as well as speedy and effective interaction between various specialties.